Injuries and illnesses of football players during the 2010 FIFA World Cup - Dvorak, J.; Junge, A.; Derman, W.; Schwellnus, M. (British Journal of Sports Medicine, 2011)
Background The incidence and characteristics of football injuries during matches in top-level international tournaments are well documented, but training injuries and illnesses during this period have rarely been studied.